The Effect of Outpatient Health Services on the Satisfaction of BPJS Health Participants at DKT Hospital (Army Health Office) Gubeng Corner Surabaya in 2023 - Ina Sukma Kasih; Deli Theo; Ramadan Syafitri Nasution (PROMOTOR, 2024)
This study evaluates the impact of outpatient services on BPJS participant satisfaction at DKT Gubeng Pojok Hospital, Surabaya. Conducted using a cross-sectional quantitative method on 95 BPJS participants from January to June 2023. The majority of respondents showed dissatisfaction with services. Analysis of variables such as responsiveness, reliability, assurance, caring, and physical evidence highlights aspects related to patient satisfaction. Logistic regression results show that responsiveness and caring have a significant relationship with patient satisfaction. The study emphasizes the need to increase the response and concern of health workers towards patients to increase BPJS participant satisfaction.